Transmathematica 2022: The 4th International Conference on Total Systems - Anderson, James; Gomide, Walter; dos Reis, Tiago (Transmathematica, 2022)
Transmathematica 2022: The 4th International Conference on Total Systems was held online, using Zoom, on 29 September 2022 at 14.45 - 18.00, London time. Edited video recordings have been uploaded to the Transmathematica channel on YouTube. We now present the conference proceedings. We note a significant offer of donations to Transmathematica and announce Transmathematica 2023: The 5th International Conference on Total Systems.